ASPH Regulates Osteogenic Differentiation and Cellular Senescence of BMSCs - Peng, Hui; Guo, Qi; Xiao, Ye; Su, Tian; Jiang, Tie-Jian; Guo, Li-Juan; Wang, Min (Frontiers in Cell and Developmental Biology, 2020)
Osteogenesis and senescence of BMSCs play great roles in age-related bone loss. However, the causes of these dysfunctions remain unclear. In this study, we identified a differentially expressed ASPH gene in middle-aged and elderly-aged groups which were obtained from GSE35955. Subsequent analysis in various databases, such as TCGA, GTEx and CCLE, revealed that ASPH had positive correlations with several osteogenic markers. The depletion of mouse Asph suppressed the capacity of osteogenic differentiation in bone marrow mesenchymal stem cells (BMSCs). Notably, the expression of ASPH in vitro decreased during aging and senescence. The deficiency of Asph accelerated cellular senescence in BMSCs. Conversely, the overexpression of Asph enhanced the capacity of osteogenic differentiation and inhibited cellular senescence. Mechanistically, ASPH regulated Wnt signaling mediated by Gsk3β. Taken together, our data established that ASPH was potentially involved in the pathogenesis of age-related bone loss through regulating cellular senescence and osteogenic differentiation, which provides some new insights to treat age-related bone loss.